The Effect of Inquiry-Based Collaborative Learning and Inquiry-Based Online Collaborative Learning on Success and Permanent Learning of Students - Nurullah Korkman; Mustafa Metin (Universitas Pendidikan Indonesia, 2021)
This study aims to specify the effect of inquiry-based collaborative learning and inquiry-based online collaborative learning methods on students' success and permanent learning. In this quantitative study, a pre-test post-test non-equalized control group model of quasi-experimental design has been used. The study's sample comprises 64 students, 32 in the experimental and 32 in the control group, determined by the stratified sampling method. The research has taken place in four stages. Firstly, an achievement test for chemical bonds subject has been applied as a pre-test to both experimental and control groups. The researchers have developed the test; it consists of 33 questions. Secondly, chemical bonds have been taught to control groups with inquiry-based collaborative learning methods and experimental groups with inquiry-based online collaborative learning methods. The achievement test has been applied to both groups as a post-test in the third stage. The same test has been applied as a retention test six weeks later. In the analysis of tests, dependent and independent samples t-test have been used in p=.05 significance level. The research results show that the inquiry-based online collaborative learning method is more effective on students' success and permanent learning than other methods.